2017
DOI: 10.1177/0956462416688127
|View full text |Cite
|
Sign up to set email alerts
|

Early clinical experience of dolutegravir in an HIV cohort in a larger teaching hospital

Abstract: Dolutegravir (DTG) is the third HIV integrase inhibitor (INI) available for prescription in Belfast since July 2014. It has shown high virological efficacy in both treatment-naïve and -experienced patients. We carried out a retrospective case chart analysis of HIV-1-positive adults commenced on DTG between July 2014 and September 2015. Patients were identified from records as either treatment-naïve or antiretroviral therapy (ART) experienced. Outcomes included: (1) virological response (HIV-1 RNA viral load at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
32
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 9 publications
(23 reference statements)
6
32
1
Order By: Relevance
“…In pre-marketing trials, DTG demonstrated favorable safety and tolerability profiles, with a <2% discontinuation rate secondary to any adverse events (AEs), comparable to raltegravir and superior to efavirenz [8,9]. However, contrasting real-life data reveal unexpectedly higher rates (7-15%, median time 72 days) [10][11][12][13][14], most commonly due to insomnia/sleep disturbances and other neuropsychiatric (NP) AEs (up to 8%), regardless of prior neuropsychiatric history, thereby implicating a potentially neurotoxic effect of DTG [14][15][16][17][18]. Comparison studies suggest that NP-AEs are commoner with DTG than other InSTIs [11,12,16].…”
Section: Introductionmentioning
confidence: 99%
“…In pre-marketing trials, DTG demonstrated favorable safety and tolerability profiles, with a <2% discontinuation rate secondary to any adverse events (AEs), comparable to raltegravir and superior to efavirenz [8,9]. However, contrasting real-life data reveal unexpectedly higher rates (7-15%, median time 72 days) [10][11][12][13][14], most commonly due to insomnia/sleep disturbances and other neuropsychiatric (NP) AEs (up to 8%), regardless of prior neuropsychiatric history, thereby implicating a potentially neurotoxic effect of DTG [14][15][16][17][18]. Comparison studies suggest that NP-AEs are commoner with DTG than other InSTIs [11,12,16].…”
Section: Introductionmentioning
confidence: 99%
“…Of those who underwent ART substitution, the most common first-line regimen was TDF plus 3TC plus efavirenz (EFV) (75%); TDF plus 3TC plus ritonavir-boosted atazanavir (28.1%) and darunavir plus raltegravir plus ritonavir (25%) were the most common second-and third-line regimens, respectively. 24 (14,80) 15 (12,18) 16 Overall, kidney function remained stable at 6 months follow-up, with median creatinine at initiation of 0.9 (IQR, 0.7-1.1), and 1.0 (IQR, 0.8-1.2) and 0.9 (IQR, 0.85-1.1) at 6 and 12 months, respectively. No patients had an increase in liver enzymes as per the National Institutes of Health/Division of Acquired Immuno Deficiency Syndrome grading scale.…”
Section: Resultsmentioning
confidence: 96%
“…5,14,15 Some observational studies have also shown good virologic outcomes in suppressed patients switching to RAL, [16][17][18] one study in patients switching to EVG, 9 and one in patients switching to DTG. 19 One cohort study reported low failure rates over two years after switching while suppressed to an INSTI-based regimen, including RAL, DTG, and EVG, though it did not compare INSTI agents. 10 Some studies have shown good virologic outcomes on RAL or DTG in heterogeneous groups comprising both suppressed and unsuppressed patients.…”
Section: Discussionmentioning
confidence: 99%